Plasma microRNA Interindividual Variability in Healthy Individuals, Pregnant Women, and an Individual with a Stably Altered Neuroendocrine Phenotype. (26th August 2021) - Max, Klaas E.A.; Wang, Victoria R.; Chang, Michael S.; Liau, Jonathan; Weiss, Zachary R.; Morgan, Stephanie; Li, Jenny; Bogardus, Kimberly A.; Morozov, Pavel; Suryawanshi, Hemant; Akat, Kemal M.; Ben-Dov, Iddo Z.; et al.
Abstract: Background: Extracellular RNAs (exRNAs) in biofluids are amenable to quantitative analysis and proposed as noninvasive biomarkers for monitoring organ function. Cell-lineage-specific microRNAs (miRNAs) are present in plasma as soluble ribonucleoproteins or enclosed in exRNA carriers and transported through the vasculature. However, more extensive studies of healthy individuals are needed to gain insights into the variability of plasma miRNA abundance and composition. Methods: The exRNA composition of platelet-depleted plasma collected twice from 236 healthy individuals was characterized by small RNA sequencing. Plasma of pregnant women featuring dramatically increased placental miRNAs and samples from subject P12 with noticeably increased epithelial- and neuroendocrine-origin miRNAs were included for comparison. The miRNA content of 10 000 g and 100 000 g pellet fractions of plasma generated by ultracentrifugation was also determined. Data analysis methods included Pearson correlation, differential gene expression, and unsupervised clustering. Results: The abundance changes for more variable miRNAs in plasma of normal individuals correlated between coexpressed cell-lineage-specific miRNAs of the liver, neuroendocrine organs, epithelial cells, and muscle. ExRNA of pellet fractions contained <2% of total plasma miRNA with modest enrichment of lineage-specific and variable miRNAs compared to supernatant. The abundance fold changes of miRNAs observed in pregnancy and P12 compared to normal exceeded interquartile variability of healthy individuals. The neuroendocrine miRNA signature of P12 persisted for more than 4 years and was absent in other individuals. Conclusions: This study defines the framework and effect size for screening of extensive plasma collections for miRNA phenotypes and biomarker discovery.